Radiation protection in the health sciences - E Noz, Marilyn (World Scientific, 2014)
Takes a practical approach to radiation protection and presents information for anyone working in the radiation field or with radioactive material. This book describes the basic principles and practical implementation recommendations of radiation protection. It includes self-assessment review questions and problems, answers, and more.